Portuguese Translation and validation of the user rating scale for mobile applications in the health area (uMARS) (Research, Society and Development, 2023)
New health apps can improve patients' lives. However, the rapid proliferation of technological solutions often does not allow a correct assessment of the quality of these tools. For these technologies, it is necessary to carry out more studies and evaluation instruments that stimulate additional research and practices to evaluate the effect of currently available tools and guarantee the quality and usability of mobile technologies. The User Mobile App Rating Scale (uMARS) is a tool that provides a comprehensive, multidimensional assessment of app quality. However, this tool is not available in Portuguese. This study aims to culturally adapt and validate the rating scale questionnaire for users from English to Portuguese. First, a qualitative study was carried out in the translation and validation of the questionnaire. In a second step, the questionnaire was made available to users of the Meu Clínicas© application. Quantitative analysis was performed using Cronbach's Alpha coefficient reliability measure. Results: The 26 questions of the questionnaire were translated in full following a methodology, as well as, all translated items were revised for grammatical terms, verb tenses and synonyms. Content validity was performed through the analysis of five specialists. The study sample consisted of 5 key users and administrative professionals from the Hospital. The instrument was applied from October to November 2022. The Portuguese version of the uMARS had a total Cronbach's alpha of 0.78. The Brazilian version of this scale demonstrated semantic, idiomatic, conceptual and cultural equivalence with the original English version, as well as adequate validity and reliability.